2021
DOI: 10.3390/cancers13215414
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Anti-Cancer Therapy: A Multimodal Therapy Governed by the Tumor Microenvironment

Abstract: The concept of cancer as a systemic disease, and the therapeutic implications of this, has gained special relevance. This concept encompasses the interactions between tumor and stromal cells and their microenvironment in the complex setting of primary tumors and metastases. These factors determine cellular co-evolution in time and space, contribute to tumor progression, and could counteract therapeutic effects. Additionally, cancer therapies can induce cellular and molecular responses in the tumor and host tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 292 publications
(340 reference statements)
0
12
0
Order By: Relevance
“…Metronomic, very low-dose chemotherapy promotes a continuous pattern of stress responses [ 55 , 123 , 124 , 125 ]. The present clinical data reveal that metronomic chemotherapy at ‘very’ low-doses limits tumor tissue plasticity by stress response, probably decreasing phenotypic heterogeneity of tumor cell niches as tissue stress generally induces a tighter phenotype [ 123 , 126 , 127 , 128 , 129 , 130 , 131 ]. Thus, metronomic chemotherapy might induce phenotypic integration of inflammation control or differentiation by editing techniques and, consecutively, may serve as an enhancer of pro-anakoinotic effects mediated by added transcriptional modulators [ 55 , 123 ].…”
Section: Specific Therapeutic Access To M-crac With Tumor Tissue Edit...mentioning
confidence: 99%
“…Metronomic, very low-dose chemotherapy promotes a continuous pattern of stress responses [ 55 , 123 , 124 , 125 ]. The present clinical data reveal that metronomic chemotherapy at ‘very’ low-doses limits tumor tissue plasticity by stress response, probably decreasing phenotypic heterogeneity of tumor cell niches as tissue stress generally induces a tighter phenotype [ 123 , 126 , 127 , 128 , 129 , 130 , 131 ]. Thus, metronomic chemotherapy might induce phenotypic integration of inflammation control or differentiation by editing techniques and, consecutively, may serve as an enhancer of pro-anakoinotic effects mediated by added transcriptional modulators [ 55 , 123 ].…”
Section: Specific Therapeutic Access To M-crac With Tumor Tissue Edit...mentioning
confidence: 99%
“…Studies have revealed that angiogenesis and immune evasion are key core issues in the tumor microenvironment for liver cancer progression and treatment failure (Motz and Coukos, 2011;Fousek et al, 2021;Pinter et al, 2021;Zhou et al, 2021). In a complex tumor microenvironment composed of hepatocytes, liver sinusoidal endothelial cells (LSECs), hepatic stellate cells (HSCs), immune cells, and extracellular matrix, the development of HCC is closely related to the infiltration of immune cells and immune evasion in the tumor microenvironment (TME) (Muñoz et al, 2021). Increasing evidence has shown that H 2 S plays a key role in the occurrence and development of HCC.…”
Section: The Effect Of H 2 S In Hepatocellular Carcinomamentioning
confidence: 99%
“…Dose accumulations associated with intolerable side effects are rare, so the medication can be administered for longer periods of time [ 11 ]. The mechanisms of action are not truly cytotoxic but rather multimodal, particularly via inhibition of angiogenesis, immunomodulation, and effects on tumor stroma [ 6 , 7 , 12 , 13 ]. It is assumed that MCT is not simply a different way of administering chemotherapy (CT) but a truly new treatment option [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%